2012
DOI: 10.1016/j.canlet.2012.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori decreases p27 expression through the delta opioid receptor-mediated inhibition of histone acetylation within the p27 promoter

Abstract: Chronic Helicobacter pylori infection is associated with the decreased expression of the gastric tumour suppressor protein p27. Because transcription of the gene p27 may be regulated epigenetically through histone acetylation, which is mediated by G-protein coupled delta opioid receptor (DOR) stimulation, we examined whether H. pylori regulates the DOR/histone acetylation/p27 promoter pathway. The levels of acetylated histone and p300, a gene-specific histone acetyltransferase within the p27 promoter, were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…However, P27 Kip1 inhibition and colony number were only partially reversed after knockdown of FoxM1 by its specific siRNA, which suggests other molecules involved in this process. One study showed that H. pylori decreased P27 Kip1 expression through delta opioid receptor-mediated inhibition of histone acetylation within the P27 Kip1 promoter (40). Other research confirmed the involvement of cytoplasmic mislocalization of P27 Kip1 induced by H. pylori in gastric cancer (41).…”
Section: Discussionmentioning
confidence: 97%
“…However, P27 Kip1 inhibition and colony number were only partially reversed after knockdown of FoxM1 by its specific siRNA, which suggests other molecules involved in this process. One study showed that H. pylori decreased P27 Kip1 expression through delta opioid receptor-mediated inhibition of histone acetylation within the P27 Kip1 promoter (40). Other research confirmed the involvement of cytoplasmic mislocalization of P27 Kip1 induced by H. pylori in gastric cancer (41).…”
Section: Discussionmentioning
confidence: 97%
“…Many results both from our laboratory and from other institutes on MENK's function of upregulating immune system at suitable dose have been reported previously. [15][16][17][18][19][20][21] Our documented record showed that considerable work of approaches with MENK on its impact on immune cells in vitro and in vivo has been done in our laboratory. [7][8][9][10][11] There are predominantly mu, delta, and kappa-3 types of opioid receptors.…”
Section: Discussionmentioning
confidence: 96%
“…H. pylori infection decreases the expression of the cell cycle inhibitor protein p27 at both transcriptional and post-translational levels. H. pylori modulates the G-protein coupled delta opioid receptor (DOR) which regulates the histone acetylation of the p27 gene (CDKN1B) [49]. In addition cagA+ H. pylori strains decrease the transcription of p27 through activation of the PI3K/Akt pathway [50].…”
Section: Discussionmentioning
confidence: 99%